The simplified carbon footprint calculation as an option for sustainability education (Training and Practice : Journal of Educational Sciences, 2018)
Due to the globalization of environmental problems, it becomes increasingly topical to quantify environmental impacts from household consumption. From the different methods available we have chosen the calculation of GHG (greenhouse gas) emissions, which is based on lifestyle connected to population activities deriving from fossil resources. We have relied on electricity consumption from the three connected lifestyle activities involving the highest energy con- sumption. Based on the strategy above the national average was calculated. The results shed light on the extent of pollution deriving from energy requiring human activities. The personal responsibility of the general public concerning environmental issues and consumer responsibi- lity are not at all negligible.